The Demand for Space Heating Energy - Nelson, Jon P. (The Review of Economics and Statistics, 1975)
PREVIOUS studies of residential and commercial energy use, exclusive of electricity, have generally found that price is not a significant determinant of demand.' This paper analyzes the demand for space heating energy using cross-sectional data by state for 1971. We find that price is a significant determinant of demand with an elasticity of approximately -0.3. In deriving this estimate, explicit attention is given to: (1) discrimination among alternative functional forms since average price data rather than marginal prices are used; and (2) specification of relationships that attempt to capture the trade-off that exists between energy inputs and housing construction and insulation materials.